Absolute quantification of Neuron-specific enolase based on surface plasmon resonance - Cui Lin; Yijie Wang; Tao Peng; Pengpeng Liu; Yuanyuan Liang; Wencheng Kang; Xiaoping Yu; Yang Song; Xuping Shentu (SLAS Discovery)
Neuron-specific enolase (NSE) is currently the most reliable biomarker for small cell lung cancer (SCLC), which is important for disease monitoring, clinical evaluation and diagnosis. However, traditional methods suffer from various disadvantages, including instability, complexity, time-consuming operations, and the necessity for standards. In this study, we developed a calibration-free concentration analysis (CFCA) method based on surface plasmon resonance (SPR) technology, to accurately quantify the active concentration of NSE without relying on any standards. Based on the principle of CFCA, the active concentration of NSE can be calculated by observing binding rate variations at two flow rates under partial mass transport limitation and combining it with the known diffusion coefficient of the NSE. Using the method of CFCA, the active concentration of NSE was determined was only 0.48 mg/mL with an intra-day repeatability of 4.75%. The method has the advantages of simplicity, rapidity, realistic analysis and ease of implementation of high-throughput automated detection. Therefore, the method is expected to become the main measurement method for protein active concentration, which will be beneficial for the development of active protein standards.